Challenges of Using Artificial Intelligence in Contract Drafting: How Should AI Legal Liability Be? - Subawa, I Made Mulyawan (Kertha Patrika; Vol 46 No 2 (2024)DO - 10.24843/KP.2024.v46.i02.p03, 2024)
Artificial Intelligence (AI) in law is applied to contract drafting. The presence of AI makes it easier for people in contract drafting and, of course, can be used by contract drafters to facilitate their work. Nevertheless, AI's actions can cause losses to the users and all parties involved. The potential for a cyberattack could happen. Meanwhile, Indonesian law does not regulate legal liability against AI. Based on this background, this study is about the use of AI in contract drafting. This research falls within the category of normative research. Data collection is done by collecting legal materials such as laws, writings, books, and journals related to contract drafting. Technical analysis of legal material is done in a qualitative descriptive manner. The use of AI in contract drafting using smart contract features is provided by Legal Tech. The presence of AI in the legal area provides ease, efficiency, and effectiveness in the completion of contract drafting. However, any substitution between human resources and AI is potentially damaging and can easily leak the parties' personal information.  While Indonesian law has not reached legal liability for the actions of AI; therefore, the analysis of AI's legal liability is carried out with the approach of the Vicarious Liability doctrine.